Digital Behaviors and Psychological Traits: Analyzing Senior High School Students' Social Media Use Through Social Studies Curriculum - Amri Dhimas Maulana; Aim Abdulkarim; Sona Minasyan (UM Purwokerto Press, 2024)
This study aims to analyze the digital behavior and psychological characteristics of high school students related to the use of social media through the perspective of the Social Science curriculum. The issue raised is how the use of social media affects social interaction and student learning at school. The method used is a qualitative approach, with data collection through in-depth interviews and observations of students and teachers at SMAN 2 Tanggul, Jember Regency. The findings show that students tend to use social media to increase engagement in discussions related to social studies materials, but also experience challenges such as impaired concentration and negative impacts on mental health. These findings indicate the need for more attention in facilitating healthy and productive use of social media in learning contexts. By understanding students' digital behaviors and psychological characteristics, this study recommends the development of more inclusive teaching strategies in the social studies curriculum, to maximize the benefits of social media as a learning tool that supports students' social and academic development.